SISTEM PENDUKUNG KEPUTUSAN PENENTUAN CUTI PEGAWAI MENGGUNAKAN METODE TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) (STUDI KASUS DI KANTOR PELAYANAN PERBENDAHARAAN NEGARA YOGYAKARTA) - Made Intan Dwipayani; Anton Setiawan Honggowibowo; Dwi Nugraheny (Compiler, 2012)
Decision Support System or DSS is a system that helps managers in solving the problems of semi-structured. Many techniques are used to make the Decision Support System, one with Fuzzy Logic. Fuzzy logic is one of problem-solving techniques where the degree of membership which are typically represented by values 0 and 1, with Fuzzy Logic is the degree of membership can be represented with a value between 0 and 1 so that it can be more balanced.             KPPN Yogyakarta in determining an employee on leave not yet have an application, and is still done manually. Therefore, to further assist in making the determination of the employee on leave should be made DSS. DSS will use fuzzy logic techniques MADM applying TOPSIS method in the calculation process. SPK expected this may be an alternative in the determination of an employee on leave in KPPN Yogyakarta later. Decision Support System determination of an employee on leave with TOPSIS method is to obtain results that are not much different from the calculations manually, so it can be applied to support the decision in the determination of employee leave.